1982
DOI: 10.1007/bf00582394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on proximal tubular acidification

Abstract: The effect of temperature on proximal tubular acidification was studied in isolated rat kidney, perfused with 20 mM phosphate Ringer's containing 7.5 g/100 ml bovine albumin, equilibrated with air. Tubular pH was measured with Sb microelectrodes during stopped-flow microperfusion. The temperature of the kidney was varied between 10 and 46 degrees C. At 10 degrees C the proximal tubule was still able to maintain pH gradients of about 0.7 pH units. However, half-times (t/2) of both acidification and alkalinizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Rubio et al found reduced H back-flux in proximal tubules of isolated perfused rat kidney at low Na + in the presence of 10 -3 M amiloride [17]. These authors also observed an effect of temperature on H + flux, activation energies of the same order (8-9 kcal/mol) being found for H + ion secretion and back-flux [18]. These data suggest that both H ion secretion and back-flux are mediated by the same carrier, the Na+/H + exchanger.…”
Section: Mechanism Of H + Ion Back-fluxmentioning
confidence: 69%
“…Rubio et al found reduced H back-flux in proximal tubules of isolated perfused rat kidney at low Na + in the presence of 10 -3 M amiloride [17]. These authors also observed an effect of temperature on H + flux, activation energies of the same order (8-9 kcal/mol) being found for H + ion secretion and back-flux [18]. These data suggest that both H ion secretion and back-flux are mediated by the same carrier, the Na+/H + exchanger.…”
Section: Mechanism Of H + Ion Back-fluxmentioning
confidence: 69%